SAT0336 The Long-Term Effects of Sysadoa Treatment on Knee Osteoarthritis Symptoms and Progression of Structural Changes: Participants from the Osteoarthritis Initiative Progression Cohort. (23rd January 2014) - Martel-Pelletier, J.; Roubille, C.; Raynauld, J.-P.; Abram, F.; Hochberg, M. C.; Dorais, M.; Delorme, P.; Pelletier, J.-P.
Abstract : Objectives: To explore the effects of commonly used medications for treatment of knee osteoarthritis (OA) on structural progression. Methods: Participants (n=600) were selected from the Osteoarthritis Initiative (OAI) progression cohort (http://www.oai.ucsf.edu/ ) (n=1, 390) who met the following criteria: 24 consecutive months of follow-up with clinical and imaging data including radiographs and magnetic resonance imaging (MRI) of the index (highest WOMAC pain) knee. Data for joint space width (JSW) were obtained from the OAI database and cartilage volume was measured using fully-automated MRI. Results: Participants reported taking (+) (n=300) or not taking (-) (n=300) OA treatment (analgesic/NSAID) over 24 months, with or without glucosamine and chondroitin sulfate (Glu/CS). The +analgesic/NSAID subjects had higher WOMAC scores (p<0.0001) and smaller JSW (p=0.013) reflecting more severe disease at baseline. In the -analgesic/NSAID group, subjects taking Glu/CS had a smaller loss of JSW at 12 months (p=0.057) and cartilage volume at 24 months in the medial central tibial plateau (p=0.022 univariate and p=0.025 multivariate analysis). In the +analgesic/NSAID group, the subjects taking Glu/CS had significantly lower WOMAC scores (pain, p<0.0001; stiffness, p=0.0373; disability, p=0.0004) and higher KOOS scores at baseline as well as a smaller cartilage volume loss in the tibial plateau at both 12 (p=0.029) and 24 months (p=0.033). In the -analgesic/NSAID groups, those who took Glu/CS and had JSW at baseline higher than the median showed less cartilage volume loss at 24 months in the medial compartment (p=0.025) and condyle (p=0.01). Conclusions: In both the +analgesic/NSAID and -analgesic/NSAID groups, participants who took Glu/CS had reduced loss of JSW and cartilage volume over 24 months. These effects of Glu/CS on structural changes support results from previous studies. Disclosure of Interest: None Declared